Fault Tolerant Control of a X8-VB Quadcopter - Brito, Vasco da Silva (2017)
In this dissertation new modeling and fault tolerant control methodologies of a quadcopter with X8 configuration are proposed; studies done to actuators faults and possible reconfigurations are also presented. The main research effort has been done to design and implement the kinematic and dynamic model of a quadcopter with X8 configuration in Simulink®. Moreover, simulation and control of the quadcopter in a virtual reality world using Simulink3D® and real world experimental results from a quadcopter assembled for this purpose. The main contributions are the modeling of a X8 architecture and a fault tolerant control approach. In order to show the performance of the controllers in closed-loop, simulation results with the model of a X8 quadcopter and real world experiments are presented. The simulations and experiments revealed good performance of the control systems due to the aircraft model quality. The conclusion of the theoretical studies done in the field of actuators’ fault tolerance were validated with simulation and real experiments.